PENGARUH MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) TERHADAP HASIL BELAJAR SISWA SMP PADA MATERI CAHAYA - Nurcahyati, Rofita Indri; Indrawati, Indrawati; Wicaksono, Iwan (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2020)
This study aims to examine the effect of PBL learning models on student learning outcomes in light material. This type of research is an experimental study with a post-test only control group design. This research was conducted at SMPN 1 Ambulu. The study population was all class VIII SMPN 1 Ambulu, sampling using a homogeneity test. Student learning outcomes data were collected using post-test questions and analyzed using the Independent Sampe T-test with a significance level of 5%. The results of data analysis on the Kolmogorov Smirnov normality test showed that the two study samples were normally distributed, so that the parametric statistical test was then the Independent Sample T-test. The results of the analysis with the Independent Sample T-test show that there is a significant influence on the PBL learning model on student learning outcomes in light material.